2012
DOI: 10.1186/1297-9686-44-5
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity, population structure and subdivision of local Balkan pig breeds in Austria, Croatia, Serbia and Bosnia-Herzegovina and its practical value in conservation programs

Abstract: BackgroundAt present the Croatian Turopolje pig population comprises about 157 breeding animals. In Austria, 324 Turopolje pigs originating from six Croatian founder animals are registered. Multiple bottlenecks have occurred in this population, one major one rather recently and several more older and moderate ones. In addition, it has been subdivided into three subpopulations, one in Austria and two in Croatia, with restricted gene flow. These specificities explain the delicate situation of this endangered Cro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
19
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 22 publications
5
19
1
Order By: Relevance
“…The population genetic indices H o and H e are similar among all analyzed genetic groups and in accordance with those reported by Druml et al (2012) for local Balkan pig breeds in Austria (Mangalica, A r = 3.8, H o = 0.58, and H e = 0.54), Croatia (Black Slovonian, A r = 5.4, H o = 0.59, and H e = 0.64 and Turopoljski Lug, A r = 3.3, H o = 0.38, and H e = 0.37), Serbia (Mangalica, A r = 3.9, H o = 0.58, and H e = 0.54), and Bosnia-Herzegovina (Bosnian mountain pig, A r = 4.2, H o = 0.62, and H e = 0.58). The observed mean allelic richness in EBP (A r = 7.70) is substantially higher than in breeds studied by Druml et al (2012) which may be explained by historical genetic introgression with wild boars.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The population genetic indices H o and H e are similar among all analyzed genetic groups and in accordance with those reported by Druml et al (2012) for local Balkan pig breeds in Austria (Mangalica, A r = 3.8, H o = 0.58, and H e = 0.54), Croatia (Black Slovonian, A r = 5.4, H o = 0.59, and H e = 0.64 and Turopoljski Lug, A r = 3.3, H o = 0.38, and H e = 0.37), Serbia (Mangalica, A r = 3.9, H o = 0.58, and H e = 0.54), and Bosnia-Herzegovina (Bosnian mountain pig, A r = 4.2, H o = 0.62, and H e = 0.58). The observed mean allelic richness in EBP (A r = 7.70) is substantially higher than in breeds studied by Druml et al (2012) which may be explained by historical genetic introgression with wild boars.…”
Section: Discussionsupporting
confidence: 91%
“…The observed mean allelic richness in EBP (A r = 7.70) is substantially higher than in breeds studied by Druml et al (2012) which may be explained by historical genetic introgression with wild boars.…”
Section: Discussionmentioning
confidence: 63%
“…Negative values of inbreeding coefficient were also observed in the Serbian Mangalica breed and in a Turopolje herd, suggesting an excess of heterozygotes due to non-random mating (Druml et al, 2012). As far as we know, the heterozygote excess in our study is among the highest ever reported.…”
Section: Discussionsupporting
confidence: 66%
“…In our study, microsatellite markers showed a considerably high degree of genetic polymorphism within and between populations on the basis of their allele numbers per locus (N A ) and their genetic heterozygosity (H E ). The mean number of alleles per locus (N A = 12.27) was the highest among several European and Asian breeds including 11 European pigs breeds (N A = 10.6) (Laval et al, 2000), the Taihu pig breed (N A = 8) (Fan et al, 2002), the Iberian pig breed (N A = 7.2) (Fabuel et al, 2004), the Cinta Senese pig breed (N A = 9) (Scali et al, 2012), the Nero Siciliano pig breed (N A = 9.96) (Guastella et al, 2010), six Chinese indigenous pig breeds (N A = 10.35) (Wang et al, 2011), and the Croatian Turopolje pig breed (N A = 7.7) (Druml et al, 2012). However, the mean number of alleles per locus was significantly higher in several Chinese indigenous pig populations (NA = 24.8) (Li et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Assessing the genetic diversity and understanding the relationships among and within populations are the first necessary steps to establish conservation priorities and strategies (Berthouly et al 2010;Druml et al 2012). Large sample sizes are usually recommended to accurately estimate population statistics.…”
Section: Discussionmentioning
confidence: 99%